2019
DOI: 10.3390/su11174590
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Heterogeneity of the Carbon Emission Effect Resulting from Urban Expansion among Three Coastal Agglomerations in China

Abstract: Land-use change, particularly urban expansion, can greatly affect the carbon balance, both from the aspects of terrestrial ecosystems and anthropogenic carbon emissions. Coastal China is a typical region of rapid urban expansion, and obvious spatial heterogeneity exists from the north to south. However, the different urban change characteristics and the effect on carbon balance remain undetermined. By unifying the spatial-temporal resolution of carbon source and sink data, we effectively compared the carbon bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…However, they are superior to similar studies on carbon emissions on a fined-spatial scale. Meanwhile, the research results further confirm that the overall level of carbon emissions in the Pearl River Delta region does increase with time [ 25 ].…”
Section: Resultsmentioning
confidence: 61%
“…However, they are superior to similar studies on carbon emissions on a fined-spatial scale. Meanwhile, the research results further confirm that the overall level of carbon emissions in the Pearl River Delta region does increase with time [ 25 ].…”
Section: Resultsmentioning
confidence: 61%
“…Tian and Zhao (2024) found that UE in the Changsha-Zhuzhou-Xiangtan Urban Agglomerations decreased in 2015-2020 compared to the previous period [79]. Meanwhile, the finding in the three coastal agglomerations in China by Wen et al (2019) also confirmed that UE is a major trend in the development of urban agglomerations [80]. Generally, affected by differences in urban resource endowment, development mode, and development direction, the UE and CEs of different cities also differ in the development process, showing spatial imbalance among regions.…”
Section: Spatiotemporal Differences In the Impact Of Ue On Ceimentioning
confidence: 99%
“…Tian and Zhao (2024) adopted Pearson correlation analysis and found that there was a high positive correlation between urban land area and CEs; that is, an increase in urban land area would lead to a simultaneous increase in CEs [79]. Xing et al (2022) also confirmed the same synergistic expansion state of UE and CEs [80]. However, such synergies will change over time.…”
Section: Spatiotemporal Differences In the Impact Of Ue On Ceimentioning
confidence: 99%
“…Nevertheless, according to Mingpao and Cable News Network (CNN), ghost towns were also found in the PRD and Beijing-Tianjin-Hebei region, which are both considered developed regions. For this study, we chose the PRD, an advanced city region in southern China adjacent to Hong Kong and Macao [59], as the case for our empirical study. PRD has a population of 56 million, with a Gross National Product (GDP) of 578 million yuan in 2014, making it one of the most developed and active areas in China.…”
Section: Study Areamentioning
confidence: 99%